DOI: 10.31274/etd-180810-2340
|View full text |Cite
|
Sign up to set email alerts
|

Fossil energy use in conventional and low-external-input cropping systems

Abstract: ErratumERRATUM low-external-input and conventional systems to refl ect the updated data set, as well as changing the primary energy input category from grain handling to fertilizer. Th e corrections change the quantitative results reported in the publication, but with the exception of a shift in the relative importance of grain handling and fertilizer, the general pattern of results and conclusions remains the same.My coauthors and I sincerely apologize for the error in the publication. -Michael CruseABSTRACT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Results of the experiment indicated that corn and soybean yields from the more diverse 3-and 4-year systems were higher than those from the conventional system, despite substantial reductions in the use of synthetic N fertilizer and herbicides [36][37][38] (Table 1). Fossil energy use decreased with increases in crop diversity due to reductions in the use of fertilizers and pesticides, gas to dry grain, and liquid fuel to power farm machinery 37 (Table 1). Weed suppression was highly effective in each of the three cropping systems as reflected by the very small amounts of weed biomass found in corn and soybean phases of the rotations 36 (Table 1).…”
Section: Lengthening Rotations To Reduce Agrichemical Use While Maintmentioning
confidence: 99%
See 4 more Smart Citations
“…Results of the experiment indicated that corn and soybean yields from the more diverse 3-and 4-year systems were higher than those from the conventional system, despite substantial reductions in the use of synthetic N fertilizer and herbicides [36][37][38] (Table 1). Fossil energy use decreased with increases in crop diversity due to reductions in the use of fertilizers and pesticides, gas to dry grain, and liquid fuel to power farm machinery 37 (Table 1). Weed suppression was highly effective in each of the three cropping systems as reflected by the very small amounts of weed biomass found in corn and soybean phases of the rotations 36 (Table 1).…”
Section: Lengthening Rotations To Reduce Agrichemical Use While Maintmentioning
confidence: 99%
“…Systems in which livestock are concentrated at high densities and isolated from the land base producing the crops that feed them are often characterized by high levels of pollution 114 . In contrast, integrated crop-livestock systems, including the diversification of cereal-based rotations with forage crops, the local application of manure, and pasture-based production, are likely to play an important role in reducing water contamination, soil erosion and fossil fuel dependence in agroecosystems, while maintaining high levels of productivity and profitability 13,37,[114][115][116] . With appropriate forms of crop diversity and integrated management systems, livestock products might be generated in a manner that permits food security to coexist with ecosystem integrity.…”
Section: Using Biodiversity To Link Agricultural Productivity With Enmentioning
confidence: 99%
See 3 more Smart Citations